2020
DOI: 10.1002/anie.202007673
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Functionalisation of Fluorophores for the Preparation of Targeted and Selective Probes

Abstract: A key current challenge in biological research is the elucidation of the that roles chemicals and chemical reactions play in cellular function and dysfunction. Of the available cellular imaging techniques, fluorescence imaging offers a balance between sensitivity and resolution, enabling the cost‐effective and rapid visualisation of model biological systems. Importantly, the use of responsive fluorescent probes in conjunction with ever‐advancing microscopy and flow cytometry techniques enables the visualisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 110 publications
0
39
0
Order By: Relevance
“…The targeting of fluorescent probes to different organelles inside cells has been widely explored. Probes equipped with empirical “tracker” groups can be simply added to cells and find their targets by different, sometimes unknown mechanisms [13, 14] . With the alternative genetic engineering approach, probes are attached to ligands for proteins that are expressed at specific sites [15] .…”
Section: Figurementioning
confidence: 99%
“…The targeting of fluorescent probes to different organelles inside cells has been widely explored. Probes equipped with empirical “tracker” groups can be simply added to cells and find their targets by different, sometimes unknown mechanisms [13, 14] . With the alternative genetic engineering approach, probes are attached to ligands for proteins that are expressed at specific sites [15] .…”
Section: Figurementioning
confidence: 99%
“…32 In addition, they can be readily synthetically modified at the imide, 4-amino-position and 3-, 5-or 6-positions of the naphthalene core. 32,33 There are some reports of fluorogenic naphthalimides for biological imaging and protein labelling, with the fluorogenic changes arising from click reactions involving azides and alkynes, 34 SNAP tags, 35 sydnones, 36 and oximes. 37 However, there are no reports of fluorogenic 4-amino-naphthalimides incorporating tetrazines for biological imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Besides tumor imaging based on passive targeting, equipping CEAF probes with affinity ligands will enable cell-specic diagnostics. 43,44 Traumatic arthritis (TA) caused by intense external force is an acute inammatory disease and its early recognition and treatment is essential for achieving effective therapeutic outcome. 45 It was reported that the inammatory response aer TA involves the recruitment of M1 macrophages with highly overexpressed integrin a v b to the articular cavity, which can be a potential biomarker for early diagnosis of TA.…”
Section: Preparation and Characterization Of The Nir-ii Functional Ceaf-nhs And A V B 3 -Specic Ceaf-rgdmentioning
confidence: 99%